Perlindungan Hukum Terhadap Pemegang Hak Desain Tata Letak Sirkuit Terpadu Dalam Perspektif Undang-Undang Republik Indonesia Nomor 32 Tahun 2000: Studi Kasus Nvidia Dengan Intel - Naufal Rafif Syahriyan; Dear Prasatika (CV. ITTC INDONESIA, 2025)
Integrated Circuit Layout Design (ICCD) is a new form of Intellectual Property Rights (IPR) that has unique characteristics and cannot be fully regulated by traditional IPR regimes such as Copyright, Patents, trademarks, or industrial designs. The need for special legal protection for ICCD is driven by advances in technology and the global economy, especially in the semiconductor industry. Legal protection for ICCD in Indonesia is regulated through Law Number 32 of 2000 which grants exclusive rights to design creators against commercial exploitation of their work, as well as protecting them from misuse of rights by other parties. The protection mechanism is carried out both through criminal law and civil law. This protection is based on the principle of originality, and is valid for 10 years from the date of receipt or first commercial exploitation.